ORIENTASI BERMUKIM MASYARAKAT PESISIR TELUK PALU PASCA BENCANA TSUNAMI (STUDI KASUS PADA KELURAHAN MAMBORO BARAT DAN KELURAHAN PANAU) - Anisa Wulandari; Iwan Alim Saputra; Exsa Putra (Jurnal Samudra Geografi, 2023)
This research aims to find out the orientation of the coastal communities of Palu Bay post-disaster of the tsunami, especially in the West Mamboro and Panau villages, and the reasons why people still live in the red zone area. This type of research is qualitative research with a spatial approach. The research subjects were people who rebuild in the red zone area. Data were collected through observation, documentation, and interviews then analyzed using data reduction, data presentation, and conclusion drawing. The results show that: (1) Community experience, almost all respondents have quite a lot of experience in tsunami-prone areas, (2) Community knowledge is obtained by respondents already having sufficient knowledge about the tsunami hazard, but the community still lacks understanding regarding what types of buildings can reduce the impact of the tsunami disaster, (3) The orientation of living or the point of view of the people who still live in the red zone area shows that the community still inhabits or returns to settle in the red zone area for different reasons where the area they currently live in is where they work to earn a living, moving they can't find their jobs that they have been working on for a long time, as for another reason people still occupy the red zone because the land they live in is currently a loss to leave..